The Effect of the Internet of Things Integrated Discovery Learning Model on Students Critical Thinking Skills: Meta-analysis - Baso Intang Sappaile; Mohammad Edy Nurtamam; Sukini; Losita Dewi; Tomi Apra Santosa (AKADEMI TEKNIK ADI KARYA, 2024)
This study aims to determine the effect of the internet of things integrated discovery learning model on students' critical thinking skills. This type of research is meta-analysis research. This research data comes from 12 national and international journals published in 2020-2024. Data tracing through goole scholar, Sage journal, Researchgate and ScienceDirect. The inclusion criteria in this meta-analysis are research derived from national and international journals indexed by SINTA and Scopus, research must be experimental methods and quasi-experiments, research related to the Internet of Things (IoT) integrated discovery learning model on students' critical thinking skills and research reports complete data to calculate effect size values. Data analysis using Microsoft Excel. The results concluded that there is an influence of the IoT integrated discovery learning model on critical thinking skills with a high mean effect size ( ES = 0.915) effect category.